2021
DOI: 10.1364/ol.426752
|View full text |Cite
|
Sign up to set email alerts
|

Hundred-watt-level phosphosilicate Raman fiber laser with less than 1% quantum defect

Abstract: Quantum defect (QD)-induced high thermal load in high-power fiber lasers can largely affect the conversion efficiency, pose a threat to the system security, and even prohibit the further power scaling. In this Letter, we investigate evolutions and influences of the reflectivity of the output coupler, the length of phosphosilicate fiber, and the pump bandwidth, and demonstrate a hundred-watt-level low-QD Raman fiber laser (RFL). The RFL enabled by the boson peak of phosphosilicate fiber achieves a maximum power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…An increased understanding of how manufacturing method influences the properties of these materials benefits new fibers generated from new compositions. Moreover, it has been reported that the quantum defect induced high thermal load in HPFLs can be effectively eliminated in phosphorus-doped fiber [480][481][482][483][484][485][486][487][488] and over the hundred-watt level fiber laser with less than 1% quantum defect [486] has been demonstrated. From a more intrinsic view of light-matter interactions, the increment of both P 2 O 5 and B 2 O 3 continues to reduce heat generation and decreases the value of dn/dT [36,37], which suppresses the induction to parasitic effects such as SBS and TMI as well.…”
Section: Summary and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased understanding of how manufacturing method influences the properties of these materials benefits new fibers generated from new compositions. Moreover, it has been reported that the quantum defect induced high thermal load in HPFLs can be effectively eliminated in phosphorus-doped fiber [480][481][482][483][484][485][486][487][488] and over the hundred-watt level fiber laser with less than 1% quantum defect [486] has been demonstrated. From a more intrinsic view of light-matter interactions, the increment of both P 2 O 5 and B 2 O 3 continues to reduce heat generation and decreases the value of dn/dT [36,37], which suppresses the induction to parasitic effects such as SBS and TMI as well.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…In addition to developing fiber lasers with higher output power and multi-dimensional controllability, there is an urgent demand for real-time analysis of laser beam characteristics, i.e., the mode decomposition (MD) [483][484][485][486][487][488][489][490][491]. Beam characterization represented by MD technology and beam quality measurement is an important tool for further study of fiber lasers.…”
Section: Summary and Prospectsmentioning
confidence: 99%